2017
DOI: 10.26603/ijspt20170812
|View full text |Cite
|
Sign up to set email alerts
|

Age Differences in Measures of Functional Movement and Performance in Highly Youth Basketball Players

Abstract: Background:There is a lack of information about the influence of age on functional movement tests (FMT) and performance tests as well as in their relationships in young basketball players. Purpose:The purpose of the present study was to determine the variations in FMT and jump and/or sprint performance scores between age groups (U-14 vs. U-16) in Highly-trained young basketball players. The second purpose was to investigate the relationship between FMT for lower body and jump and/or sprint performance in highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 25 publications
4
23
0
Order By: Relevance
“…These findings contradict the influence of age on other measures of dynamic postural control such as the SEBT, where reach measurements increase with age (Holden et al, 2016; Gonzalo-Skok et al, 2017; McCann et al, 2017). However, these findings are based on young populations.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…These findings contradict the influence of age on other measures of dynamic postural control such as the SEBT, where reach measurements increase with age (Holden et al, 2016; Gonzalo-Skok et al, 2017; McCann et al, 2017). However, these findings are based on young populations.…”
Section: Discussionmentioning
confidence: 83%
“…However, these findings are based on young populations. Older basketball players (16 years) had increased SEBT measurements in some directions when compared to younger players (14 years) (Gonzalo-Skok et al, 2017). In a similar age group Holden and co-workers reported that 13-year-olds increased all SEBT reaches tested over a 24-months period (Holden et al, 2016), while McCann and co-authors reported that older (20 years) had greater SEBT reach measures than younger (15 years) football players (McCann et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations